Perceptions and Practice of Labor Pain-Relief Methods among Health Professionals Conducting Delivery in Minia Maternity Units in Egypt - Ola Mousa; Amal Ahmed Abdelhafez; Ahmed R. Abdelraheim; Ayman M. Yousef; Ahmed A. Ghaney; Saad El Gelany (Obstetrics and Gynecology International)
Introduction. In low-resource settings (LRSs), pain relief during labor is often neglected. Women and health professionals (HPs) may lack awareness of analgesic options, may not accept these options, or may have concerns regarding their safety. Furthermore, even if women or HPs preferred labor analgesia, options may not be available at the hospital. This study was carried out to explore how HPs perceive and practice pain management during labor in Minia maternity units in Egypt. Methods. A structured, self-administered questionnaire from 306 HPs in Minia maternity units from August 1, 2016, to August 30, 2017, after approval by the organizational Ethical Review Committee. Results. The response rate was 76.5%. The majority, 78.2% of participants, believed in pain relief during labor. However, their practices are different. In the first stage of labor, almost 44.9% used nonpharmacological methods, whereas 36.8% used neither pharmacological nor nonpharmacological methods. Hospital-related factors were the major barriers against using pain-relief methods, as stated by HPs. Conclusion. Although most HPs understand the role of analgesia in labor pain relief, there is a wide gap between the use of pain-relief methods and women’s need in Minia, Egypt; HPs claim this is due to health care facilities. There is an urgent need to identify the barriers against and raise the awareness among the community and HPs of the need to use pain-relief methods as part of improving the quality of care during labor.